Comparative Study on the Total Phenolic Content and Radical Scavenging Activity of Common Edible Vegetable Oils. Issue 1 (30th January 2013) - Janu, Chandran; Kumar, D.R. Soban; Reshma, M.V.; Jayamurthy, P.; Sundaresan, A.; Nisha, P.
Abstract The study investigates the antioxidant potential of commonly used vegetable oils viz., coconut (CNO), sunflower (SFO), rice bran (RBO), groundnut (GNO), sesame (SESO) and mustard oil (MO), where the oils were extracted with methanol; and these methanolic extracts were used for the antioxidant studies. Fatty acid composition by gas chromatography, physicochemical parameters such as specific gravity, refractive index, acid value, iodine value and peroxide value were also analysed. Total phenolic content (TPC) and antioxidant activities of the oils (DPPH, ABTS, superoxide and nitric oxide radical scavenging assays) were evaluated. Phenolic compounds were identified by high‐pressure liquid chromatography (HPLC). Percentage TPC was highest in groundnut oil with 3.09 mg/100 g oil followed by coconut oil, rice bran oil, mustard oil, sunflower oil and sesame oil with 1.8, 0.89, 0.56, 0.49 and 0.33 mg/100 g oil, respectively. The methanolic extracts of oils showed potential antioxidant activity in terms of super oxide and nitric oxide radical scavenging activity. Practical Applications The present study indicated that vegetable oils can contribute to the dietary intake of antioxidants, depending on the processing condition. This is the first study of its kind to investigate and compare the phenolic content by HPLC and also the radical scavenging activity (DPPH, ABTS, superoxide and nitric oxide) of different oils. It was observed that the unrefined oils posses better antioxidant activity than the refined oils, which imply the importance of optimizing and/or modifying the existing steps in the vegetable oil processing to retain the polyphenolic content in vegetable oil without compromising other physicochemical parameters. The study has brought out the importance of polyphenolic compounds in vegetable oil as radical scavenging agents that could be beneficial in the management of many degenerative diseases. This may provide vegetable oils a new dimension in health management other than its traditional uses.